Effect of vitamin A on severity of acute diarrhea in children - Marlisye Marpaung; Supriatmo Supriatmo; Atan Baas Sinuhaji (Indonesian Pediatric Society, 2013)
Background Vitamin A deficiency may increase the risk or bea cause of diarrhea. Many studies have been conducted on theefficacy of vitamin A in the management of acute diarrhea, butthe outcomes remain inconclusive.Objective To determine the effectiveness of vitamin A in reducingthe severity of acute diarrhea in children.Methods We performed a singleô€ˆblindô€ˆrandomized controlledtrial in the Secanggang District, Langkat Regency, North ofSumatera, from August 2009 to January 2010 in children aged6 months to 5 years, who had diarrheas. Subjects were dividedinto two groups. Group 1 received a single dose of vitamin A(100,000 IU for subjects aged 6 to 11 month old or with bodyweights :s 10 kg, or 200,000 IU for subjects aged 2: 12 month oldor with body weights> 10 kg). Group 2 received a single doseof placebo. The establishment of severity was based on changesin diarrheal frequency, stool consistency, volume and durationof diarrhea after treatment. We performed independent Tô€ˆtestand Chi square tests for statistical analyses. The study was anintentionô€ˆtoô€ˆtreat analysis.Results We enrolled 120 children who were randomized intotwo groups of 60 subjects each. Group 1, received vitamin Aand group 2 received a placebo. The results showed significantdifferences between the two groups in stool volume starting onthe first day (95%CI 192.30 to 3237.51; Pô€‰O.OOI), as well asdiarrheal frequency (P=O.OOl) and stool consistency (P=O.OOl)on the second day observation and duration of diarrhea followingtreatment (95%CI - 40.60 to - 25.79; Pô€‰O.OOI;).Conclusions Vitamin A supplementation is effective in reducingthe severity of acute diarrhea in children under five years of age.[Paediatr lndones. 2013;53:125-31.]